Bone marrow necrosis: literature review - Tamara C. S. Cabral; Carolina M. Fernandes; Luis Alberto C. Lage; Maria Claudia Zerbini; Juliana Pereira
ABSTRACT Introduction: Bone marrow necrosis (BMN) is a rare pathologic entity that is commonly undiagnosed, and often associated with hematologic diseases. Methodology: We conducted a literature review at PubMed using "bone marrow necrosis" as key words. Our search retrieved 25 articles written in English, and a further 65 case reports. Results and discussion: BMN pathophysiology is not well understood, but appears to be associated with vascular injuries that lead to oxygen and nutrient deprivation. Destructive tumor necrosis factor alpha (TNF-α) activity is also likely involved in the development of endothelial and bone marrow sinusoidal lesions. Diagnoses of BMN are commonly indicated by anemia, thrombocytopenia, high levels of lactic dehydrogenase and alkaline phosphatase, and the identification of leukoerythroblastic reactions. Bone marrow (BM) aspirate and biopsy, and magnetic nuclear resonance imaging are the main diagnostic options. The only available treatments are those directed against the primary cause, with associated supportive care for what is ordinarily a rapidly lethal state. Conclusion: The search for an underlying associated malignancy is important for the management of BMN.